Titania-Coated Magnetite Particles for as(V) Removal from Water - Kumari Devaraj, Nisha; Srinath Ganapathe, Lokesh; Riyad Elghazali, Samer; S.M. Mukter-Uz-Zaman, A.; Hin Yong, Wong (International Journal of Engineering and Technology, 2018)
Surface-modified magnetite (Fe3O4) particles are being proposed as adsorbents for arsenic (As) contaminated water due to its exploitable magnetic properties. In this study, magnetite particles were synthesised using co-precipitation method at various stirring times to obtain particles of different sizes. The particles were subsequently coated with titanium dioxide. Particle size analyser measurements indicated increase in the particles size with the increase in stirring time from 30 to 60 mins. Based on the X-ray diffractometer characterisation results, the obtained peaks were ascribed to that of magnetite. Titanium dioxide peaks were clearly evident for the titania-coated particles. The As(V) removal performance of the particles was tested using the low-cost molybdenum blue-based colorimeter method assisted by a UV-Vis spectroscopy. Prior to the testing, a calibration curve was obtained using As(V) sample solutions with different concentrations which depicted a linear relationship between the peak absorbance values and the concentration. Results indicated that all the titania-coated magnetite particles were able to remove 100% of As(V) in the tested solution for a contact time of 4 hours. The high affinity of the outer-titania shell towards As (V) ions may be beneficial to obtain an efficient adsorbent material for the removal of toxic As ions from water.Â Â Â